Seasonal anomalies in Arctic sea ice and their association with Northern Hemisphere climate variability, on interannual timescales in EC-earth model simulations - Levine, Xavier J.; Cvijanovic, Ivana; Montilla, Pablo Ortega; Donat, Markus G. (Zenodo, 2019)
Over the past decades, the Arctic has experienced rapid warming and extensive loss of sea ice cover. These high-latitude changes have been accompanied by extreme weather events over the Arctic and mid-latitude regions (e.g. Scandinavian 2018 summer heat wave). Yet links between the Arctic sea ice cover changes and extreme weather events (droughts, floods, cold outbreaks, heatwaves, extreme snowfall), remain poorly understood. More generally, it is unclear whether Arctic sea ice variability contributes significantly to interannual variations in extreme weather events in mid- and high-latitude regions. Using an ensemble of EC-Earth coupled climate model simulations we explore the association of the seasonal-mean Arctic sea ice cover with extreme anomalies in the surface climate (on seasonal and intraseasonal timescales). We first assess these teleconnections in a set of pre-CMIP6 (H2020 PRIMAVERA) simulations in which sea ice cover evolves freely. Results are compared across different forcing boundary conditions (fixed present-day, historical and future scenarios), and horizontal spatial resolutions (1° vs 0.25° in ocean/atmosphere). Co-variability patterns of surface extreme climate with sea ice cover obtained from these different PRIMAVERA simulations are finally compared to a preliminary set of CMIP6 (PAMIP) simulations in which sea ice cover is prescribed and held invariant across years, allowing us to better establish causation in the climate system.